Risk Evaluation of Immediate Surgical Failure During Thigh Hemodialysis Graft Placement by Sonographic Screening. (12th August 2015) - Little, Mark D.; Allon, Michael; McNamara, Michelle M.; Ong, Song; Lockhart, Mark E.; Young, Carlton J.; Robbin, Michelle L.
Abstract : Objectives: The purpose of this study was to determine whether preoperative sonographic evaluation of vascular diameters and calcification identifies patients at risk for immediate technical failure of thigh hemodialysis grafts. Methods: A retrospective analysis of 143 chronic hemodialysis patients who underwent thigh graft placement was performed. All patients underwent preoperative sonography to assess arterial and venous waveforms and vascular diameters. The degree of arterial calcification was assessed retrospectively. Patient characteristics and graft outcomes were examined. Statistical analyses were performed, with P < .05 considered clinically significant. Results: Sonography identified no or mild arterial calcification in 113 of 143 patients (79%) and moderate to severe calcification in 30 of 143 patients (21%). Primary surgical technical failure occurred in 23% of patients (7 of 30) with moderate to severe calcification, compared to 3.5% (4 of 113) of those with no or mild calcification (hazard ratio, 6.59; 95% confidence interval, 2.06–21.05; P = .002). Cumulative graft survival (time to permanent failure) was shorter in patients with moderate to severe arterial calcification (3‐year graft survival, 37% versus 56%; hazard ratio, 2.32; 95% confidence interval, 1.48–6.69; P = .003) but was not significantly associated with venous ( P = .82) or arterial ( P = .43) diameters. Conclusions: Preoperative sonographic assessment of thigh vessel diameters and calcification can identify patients who may be at risk for immediate technical graft failure and decreased cumulative graft survival. The use of sonography as a screening examination may improve preoperative assessment and surgical planning of hemodialysis thigh grafts.